When teaching fails due to third-party interference: a blackgirl Warrior's story. Issue 4 (1st October 2020) - Hendrix, Katherine Grace
ABSTRACT: Every instructor has experienced teaching failures in the classroom. We often conceptualize those experiences as emanating from self, and sometimes we surmise the disconnect is on our student's end. However, rarely do we consider the impact of interference from an ill-spirited colleague, in my case, ill-spirited, racist colleagues. Professors of color in white postsecondary settings work to cultivate learning while simultaneously contending with what Feagin refers to as a white racial frame that is tightly woven into Western civilization with recognizable patterns at societal, institutional, and individual levels. The socially sanctioned racial bullying contributing to my birth as a blackgirl Warrior is explored in my stories of the Troll by the Bridge and the Siren.